Evaluation of Exotic Sesame Germplasm for their Resistance Against (Antigastra catalaunalis) Duponchel - , N. Swetha, T. Boopathi, C. Narendra Reddy, Praduman Yadav (Archives of Current Research International, 2024)
Aims: To evaluate 132 USDA germplasm for their resistance against sesame leaf webber A. catalaunalis. Study Design: Randomized Block Design (RBD). Methodology: Leaf webber incidence was recorded weekly in two seasons (2023, 2024) and the percent leaf damage was calculated. The data was subjected to statistical analysis. The germplasm were categorized based on the percent leaf damage in both seasons using a 1-9 scoring methodology. The combined mean analysis was also carried out, to obtain unbiased results. the germplasm were also categorized based on the combined analysis. Results: In season 1, leaf damage by sesame leaf webber ranged from 0% to 97.96%, with PI 170757, PI 223014, and PI 285170 being pest-free, while PI 170726 had the highest damage (97.96%). Germplasm were categorized as highly resistant (48), resistant (31), moderately resistant (25), susceptible (13) and highly susceptible (15). In season 2, damage ranged from 0% to 97.30%, with PI 152498, PI 158045, PI 170757, PI 223014, and PI 285170 being pest-free and PI 170726 again having the highest damage (97.30%). Germplasm were categorized as highly resistant (35), resistant (36), moderately resistant (33), susceptible (12) and highly susceptible (16). Based on combined mean value analysis, The germplasm were categorized as highly resistant (28), resistant (54), moderately resistant (21), susceptible (11), and highly susceptible (18). Conclusion: The germplasm PI 170757, PI 223014, and PI 285170 were completely free from pest damage in both seasons and also based on combined mean analysis. Thus these germplasm are highly resistant against sesame leaf webber.